MOTIVASI KELOMPOK WANITA TANI DALAM PENGOLAHAN TEPUNG CASSAVA DI KECAMATAN CIBADAK KABUPATEN LEBAK PROVINSI BANTEN - M.Y. Samber; Nawangwulan Widyastuti; A. Musyadar (Jurnal Penyuluhan Pertanian, 2020)
Cassava flour is the alternative of carbohydrate source as the subtitute of flour. The productivity of cassava (Manihot esculenta) is higher than the other agricultural commodities in Cibadak. This research is aimed to: (1) evaluate the motivation level from the woman farmers group in producing the cassava to be cassava flour in Keduagung Barat village and Pasar Keong Subdistrict Cibadak village (2) analyze factors which are influencing the motivation level of woman farmers group to produce cassava to be cassava flour in Keduagung Barat village and Keong Market Subdistrict Cibadak, (3 Determine which is the lowest aspect during the production technique in producing cassava to be cassava flour for the woman farmers group in Keduagung Barat dan Pasar Keong village, as the material in penyuluhan. This research was conducted in october 2011 until december 2011. The result of this research showed (1) The level of woman farmers group motivation in cassava flours production is included in high category, (2)Based on the factors that are influencing the farmers motivation level,the age of woman farmers group is included in the productive age category, the formal education is included in the low category, the non formal education in this case extension,is included in low category, training is included in middle category, wide area is included in very narrow category, innovation adjustment included in match category, the quality of cassava is included in good enough category and the way in using the cassava flours production tools is included in the easy use category, and (3) cassava production variable, demand, price, and transportation facilitation of cassava doesn't have a significant correlation with the woman farmers group motivation.